Plantas medicinais como recurso didático no ensino de química orgânica - Maia, Zaíde Cunha (2019)
The research presented here brings the inter and transdisciplinary theme "Medicinal Plants" in the form of a contextualized proposal, aiming to contribute to the significant learning in the teaching of Organic Chemistry, as well as to the integral formation of the student, and not only, for the cognitive development. The study was carried out at the Federal Institute of Education, Science and Technology of Ceará (IFCE) in the city of Sobral-CE, with students of the Food Technology course. We used complementary and experimental activities, in the form of field lessons and workshops that were offered to the students, in search of learning in a meaningful way. It was proposed to the participating students, the search for information related to biodiversity, popular knowledge of local culture and the content of Organic Chemistry seen in traditional lectures. For the accomplishment of this research, we opted for a qualitative research study. The experimental approach was defined as a procedure. The analyzes were made by comparing the students' initial and final knowledge tests. This work confirms that the theme "Medicinal Plants" can be applied successfully as didactic resource in the teaching of Chemistry, especially Organic Chemistry. The didactic resource used proved to be efficient to alleviate the obstacles manifested in the understanding of formulas, and in the recognition of functional groups, achieving results that allowed the students to construct the knowledge with a meaningful learning through practical experiences. In addition, this work allowed contextualizing the teaching of Organic Chemistry from life experiences that went beyond the physical limits of the classroom and culminated in relevant information compiled in the educational product entitled " Cartilha de plantas medicinais: sabedoria popular e conhecimento científico para o ensino das funções orgânicas.”